2012
DOI: 10.1080/10810730.2012.713442
|View full text |Cite
|
Sign up to set email alerts
|

The Health Literacy Skills Framework

Abstract: Health literacy is on the public health agenda. The goal to "improve the health literacy of the population" was included as an objective in Healthy People 2010 and 2020 Objectives. In 2004, the Institute of Medicine released Health Literacy: A Prescription to End Confusion, which recommended that "the Department of Health and Human Services and other government and private funders should support research leading to the development of causal models explaining the relationship among health literacy, the educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
260
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(275 citation statements)
references
References 30 publications
9
260
1
5
Order By: Relevance
“…Health knowledge has positive strong influence on health literacy as well. In this research, health knowledge is defined as an individual's knowledge at the time before reading, watching or listening to the health-related materials, which some researchers called prior knowledge (Baker, 2006;McCormack, 2009;Squiers et al, 2012). The present finding suggested that greater health knowledge leads to greater health literacy.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Health knowledge has positive strong influence on health literacy as well. In this research, health knowledge is defined as an individual's knowledge at the time before reading, watching or listening to the health-related materials, which some researchers called prior knowledge (Baker, 2006;McCormack, 2009;Squiers et al, 2012). The present finding suggested that greater health knowledge leads to greater health literacy.…”
Section: Discussionmentioning
confidence: 64%
“…Several researches have focused on theoretical explanations of potential mechanisms among these variables (Baker, 2006;Paasche-Orlow & Wolf, 2007;Sorensen et al, 2012;Squiers, Peinado, Berkman, Boudewyns, & McCormack, 2012;von Wagner, Steptoe, Wolf, & Wardle, 2009). McCormack and colleagues established a conceptual framework for individual health literacy (McCormack, 2009;Squiers et al, 2012).…”
Section: Relationships Of Health Literacy Health Behavior and Healtmentioning
confidence: 99%
See 1 more Smart Citation
“…Health literacy is defined by Berkman, Davis, and McCormack (2010, p. 16) as "the degree to which individuals can obtain, process, understand, and communicate about health-related information needed to make informed health decisions." Although the current literature shows little agreement upon the precise definition and conceptualization of health literacy (for recent conceptual models, see Sørensen et al, 2012;Squiers, Peinado, Berkman, Boudewyns, & McCormack, 2012), people's understanding of health information is usually a key component. In the frameworks, health literacy is positively associated with people's ability to understand information about health.…”
mentioning
confidence: 99%
“…Insight into the mediators of this association would also be of great value because these might be targets for interventions. Potential mediators of the association between health literacy and health behaviors include attitude towards health behaviors, self-efficacy to perform health behaviors, and perception of the risk of not performing sufficient health behaviors (Adams et al, 2013;Squiers, Peinado, Berkman, Boudewyns, & McCormack, 2012), but evidence on the role of these social cognitive factors is scarce. Regarding attitudes, only one cross-sectional study is available, which suggests an association between inadequate health literacy and negative attitudes toward health and health care .…”
mentioning
confidence: 99%